Assessing the knowledge, preparedness and perceived barriers among dental clinicians and academicians regarding tobacco cessation counselling in Chennai city- a cross-sectional study - Balasundaram, Ravisankar; Sundaram, Sounthariya Angamuthu Shanmuga; Sivakumar, Kokila; Kumar, Rajeswary; Subramanian, Kalaivani (International Journal Of Community Medicine And Public Health, 2024)
Background: Every year, tobacco usage causes three million deaths worldwide. Specialized counselling enhances the rate of cessation by an additional 4-7% when compared to standard counselling. Nowadays, the evaluation of oral health includes tobacco cessation. The goal of the study was to evaluate the knowledge, readiness, and perceived barriers of Chennai’s dentistry practitioners with reference to tobacco cessation counselling. Methods: Over the course of three months, from March to May 2024, an across-sectional questionnaire survey was carried out among dental professionals in Chennai city, comprising researchers (group 1), practitioners (group 2), and academicians and practitioners combined (group 3). A semi-open, coded, structured, self-administered questionnaire was mailed to them, and it was analysed. Results: It appears from the study’s findings that nearly every group felt that they could assist patients in quitting smoking. All of the perceived barriers to our study have been overcome after counselling, 75.9% of academicians and practitioners combined experts received good comments from patients and 70.9% of academicians felt that the patient’s chances of quitting had increased. On the other hand, 42.9% of academicians and practitioners combined professionals thought they didn’t have enough time to provide patients advice. Conclusions: Compared to academicians and clinicians in other groups, dental professionals in academicians and practitioners combined group possess superior knowledge and actively engage with patient cessation. This is evident from the results of our study. Thus, at the community and institutional levels, there is an urgent need to raise awareness and provide academicians and physicians with training.